2011
DOI: 10.2166/ws.2011.044
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and health concerns regarding the quality of water in a poor suburb of Kinshasa in the Democratic Republic of Congo

Abstract: In many developing countries, the scarcity of potable water is an ongoing challenge. Even when water is plentiful, its quality may be unsuitable for household use such as in the city of Kinshasa in the Democratic Republic of Congo (DRC) which is the study area for this investigation. Shortage of potable water has forced inhabitants in the city to rely on water wells dug without adherence to regulations or specifications within perimeters of their homesteads. The water from such wells is often polluted with hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Changes in nitrate show a mixed picture with higher maximum concentrations in two studies from Uganda and DRC (Kulabako et al 2007;Vala et al 2011) during the wet season, while in the case study from Zimbabwe (Mangore and Taigbenu 2004) lower maximum values were found. Median values for nitrate were lower in the wet season for both the Uganda and Zimbabwe case studies (see Table S1 of the ESM), which may indicate a dilution effect, while the higher maximum concentrations may be explained as a result of a pulse of contaminants at the start of the rainy season and or evaporative effects during the dry season.…”
Section: Seasonal Trends In Groundwater Quality and Implications For mentioning
confidence: 81%
See 1 more Smart Citation
“…Changes in nitrate show a mixed picture with higher maximum concentrations in two studies from Uganda and DRC (Kulabako et al 2007;Vala et al 2011) during the wet season, while in the case study from Zimbabwe (Mangore and Taigbenu 2004) lower maximum values were found. Median values for nitrate were lower in the wet season for both the Uganda and Zimbabwe case studies (see Table S1 of the ESM), which may indicate a dilution effect, while the higher maximum concentrations may be explained as a result of a pulse of contaminants at the start of the rainy season and or evaporative effects during the dry season.…”
Section: Seasonal Trends In Groundwater Quality and Implications For mentioning
confidence: 81%
“…This suggests the potential for denitrification in shallow groundwater. Nitrate has been used successfully to characterise urban loading to groundwater from a range of sources including pit latrines (Cissé Faye et al 2004;Tijani and Onodera 2005) and landfills (Ugbaja and Edet 2004;Vala et al 2011) and was applied to look at impacts on groundwater quality across different population densities (Goshu and Akoma 2011;Goshu et al 2010;Orebiyi et al 2010). There are other sources of N loading to groundwater in growing urban areas including the impact of deforestations, and these have been delineated using N:Cl ratios and in a few examples by using δ 15 N analysis (Faillat 1990).…”
Section: Nitrate and Chloridementioning
confidence: 99%
“…Studies of groundwater quality across Africa are numerous, and include rural (Grimason et al, 2013), urban (Mangore andTaigbenu, 2004) and peri-urban (Mokuolu et al, 2017), as well as agricultural (Esterhuizen et al, 2014), industrial (Takem et al, 2015) and domestic (Vala et al, 2011) studies. Most of these studies reveal decreases in groundwater quality related to human activities at the surface.…”
Section: Introductionmentioning
confidence: 99%